Evaluation of bond strength of splinting materials to the teeth using three adhesive systems-an in vitro study - Tina Puthen Purayil; Arumugam Chakravarthy; Kishore Ginjupalli; Nidambur Vasudeva Ballal (Wolters Kluwer Medknow Publications, 2015)
Aim: To evaluate the bond strength of two splinting materials (orthodontic wire and ribbond) to the tooth structure using cyanoacrylate (CA) ester, self-adhering flowable composite (Vertise flow) and conventional flowable composite as adhesives. Materials and Methods: A total of 120 human central incisors free of any carious lesions were selected for the study. To obtain the specimens, 120 human central incisors were embedded in the blocks of rapid polymerizing self-cure acrylic resin with two teeth each. The specimens were divided into six groups with ten specimens each. Group I-Orthodontic wire bonded with CA, Group II-Orthodontic wire bonded with flowable composite Group III-Orthodontic wire bonded with Vertise flow, Group IV-Ribbond bonded with CA, Group V-Ribbond bonded with flowable composite and Group VI-Ribbond bonded with Vertise flow. The adhesive force in newtons to debond the splinting material was measured in tension using universal testing machine. The force at which the splint system failed was noted. The data obtained were statistically analyzed using one-way ANOVA and significant differences were subjected to Tukey's post-hoc test at a confidence interval of 0.05. Results: Bond strength with the orthodontic wire groups was significantly less compared with Ribbond groups p < 0.05. Among the adhesives, CA demonstrated lower bond strength value as compared to Vertise flow and flowable composite p < 0.05. Conclusion: Orthodontic wire groups demonstrated significantly lower bond strength compared to ribbond groups. Among the adhesives CAs showed significantly lower bond strength compared to Vertise flow and conventional flowable composite.